2006
DOI: 10.2500/ajr.2006.20.2849
|View full text |Cite
|
Sign up to set email alerts
|

Association of Nasopharyngeal and Laryngopharyngeal Reflux with Postnasal Drip Symptomatology in Patients with and without Rhinosinusitis

Abstract: Objective evidence of NPR and LPR exists in patients reporting PND. Reflux treatment may reduce PND complaints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 34 publications
2
61
0
1
Order By: Relevance
“…Our results were supported by another study that used SNOT-20 on reXux patients, which apparently only considered diVerences in postnasal drip (PND) between the patients and the controls [30].…”
Section: Discussionsupporting
confidence: 83%
“…Our results were supported by another study that used SNOT-20 on reXux patients, which apparently only considered diVerences in postnasal drip (PND) between the patients and the controls [30].…”
Section: Discussionsupporting
confidence: 83%
“…47 One study found that patients with LPR had higher scores on the Sinonasal Outcome Test (SNOT-20), even in the absence of a diagnosis of CRS, 48 and another study showed that patients with LPR had higher scores for postnasal drainage. 49 Some of this association could be due to overlapping symptoms between LPR and CRS. However, a higher frequency of LPR determined by means of dual-channel 24-hour pH monitoring was found in a group of patients with CRS who had persistent CRS symptoms despite endoscopic sinus surgery 50 and a similarly higher frequency of LPR by pH monitoring and fluorometric pepsin assay of nasal secretions was found in a population of patients with CRS undergoing sinus surgery compared with a control group.…”
Section: Humoral or Innate Immune Deficiencymentioning
confidence: 99%
“…1 There exists a clear association between SERD and respiratory symptoms, including throat clearing, cough, asthma, postnasal drainage (PND), sinusitis, laryngopharyngitis, and sleep disturbance. [2][3][4][5] Many of these are frequent complaints among patients who seek consultation from an allergist. In one study, over half of patients presenting with throat clearing, PND, or excessive throat mucus and normal sinus imaging were found to have SERD by 24-hour pH monitoring.…”
Section: Introductionmentioning
confidence: 99%